Skrining Pemeriksaan Gula Darah, Kolesterol dan Asam Urat pada Anggota Yayasan Jantung Indonesia Cabang Papua - Indra Taufik Sahli; Asrianto Asrianto; Risda Hartati; Fajar Bakti Kurniawan; Afika Herma Wardani; Rina Purwati; Leberina Kawaitow (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2026)
Non-communicable diseases (NCDs) such as diabetes, hypercholesterolemia, and hyperuricemia pose a significant public health threat in Papua, with diabetes prevalence in Jayapura reaching 13.5% and elevated cholesterol levels at 33.9%. The lack of early detection data and limited access to healthcare services highlight the urgent need for preventive screening and health education. This activity aimed to identify metabolic risk factors blood glucose, cholesterol, and uric acid levels among the Papua Healthy Heart Foundation members. The implementation method included preparing calibrated equipment and conducting screening activities on November 9, 2024. Screening results were analyzed based on sex and age group. Findings revealed that 20.9% of female and 50% of male participants had abnormal glucose levels, while 40.9% of women and 50% of men presented with elevated cholesterol. The prevalence of hyperuricemia was lower among men (16.7%) than among women (41.7%). Interestingly, individuals aged over 60 demonstrated better metabolic control than younger age groups. The study concludes that adults aged 40–60 represent the highest-risk population. Therefore, targeted nutritional education and regular health monitoring are essential to reduce the burden of NCDs. These findings provide a foundational basis for designing locally tailored intervention programs.